Coaching Marketing Online dan Pencatatan Keuangan Terpadu Usaha Mikro dan Kecil Menengah (UMKM) pada Yayasan Tugas Ibu Tangerang Selatan - Dewi Pudji Rahayu; Deni Adha Akbari (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2018)
This Community devotion activities aim to purpose given understanding about online marketing and accounting recording so to support the business activities to mothers that are joined in Yayasan Tugas Ibu (YTI) in Tangerang South. Besides to training, monitoring and evaluation are also to ensure level their ability to apply the knowledge which they have learned. This activity is followed by twenty Micro business and Small Medium Enterprises (MSMEs) that incorporated of YTI as well YTIpartners who already owns the business. Participants are very enthusiastic with the given material. Participants admitted to many benefits of this activity and for the event the same to can be done again with advanced materials. Participants understand its importance that systematic in supporting their business.